2015
DOI: 10.1089/scd.2015.0052
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic Stem Cell-Related Protein L1TD1 Is Required for Cell Viability, Neurosphere Formation, and Chemoresistance in Medulloblastoma

Abstract: Misexpression of stem cell-related genes may occur in some cancer cells, influencing patient's prognosis. This is the case of medulloblastoma, a common and clinically challenging malignant tumor of the central nervous system, where expression of the pluripotency factor, OCT4, is correlated with poor survival. A downstream target of OCT4, L1TD1 (LINE-1 type transposase domain-containing protein 1 family member), encodes a novel embryonic stem cell (ESC)-related protein involved in pluripotency and self-renewal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 34 publications
(31 reference statements)
2
6
1
Order By: Relevance
“…Expression of L1TD1 at high levels in colon cancer cells led us to hypothesize that high expression of L1TD1 in colon cancer might be associated with prognosis. Earlier reports have demonstrated the association of stem cell pluripotency factors with poor prognosis in different cancer types, including medulloblastoma [30] and seminoma [15]. Interestingly, our results were in contrast with previous studies, suggesting that in colon cancer, high expression of L1TD1 is linked to better prognosis.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Expression of L1TD1 at high levels in colon cancer cells led us to hypothesize that high expression of L1TD1 in colon cancer might be associated with prognosis. Earlier reports have demonstrated the association of stem cell pluripotency factors with poor prognosis in different cancer types, including medulloblastoma [30] and seminoma [15]. Interestingly, our results were in contrast with previous studies, suggesting that in colon cancer, high expression of L1TD1 is linked to better prognosis.…”
Section: Discussioncontrasting
confidence: 99%
“…This points to the potential participation of L1TD1 ’s interaction partners in the contrasting prognostic outcome. This was further supported by a recent study in medulloblastoma, showing an association of high L1TD1 expression with poor clinical outcome and significant co-expression between L1TD1 and its interaction partner OCT4 [30]. Together, these findings suggest that the co-expression of L1TD1 with its interaction partners might be required for manifesting an aggressive and detrimental phenotype.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…It is highly expressed in medulloblastoma cells where it is associated with cell viability, chemotherapeutic drug resistance and stem cell-like properties [38]. …”
Section: Discussionmentioning
confidence: 99%
“…For this particular purpose, a better knowledge of the basic biology of this important embryonal CNS tumor is crucial. Previous independent studies have shown an intriguing abnormal expression of the pluripotency-related genes POU5F1 / OCT4 [7], LIN28B [8], SOX2 [9] and L1TD1 [10], in medulloblastoma. In all cases, an aberrant overexpression of either gene was significantly correlated with poor survival.…”
Section: Introductionmentioning
confidence: 99%